2011
DOI: 10.4049/jimmunol.1003715
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Stimulation Drives Human Naive and Effector Regulatory T Cells into a Th17-Like Phenotype with Reduced Suppressive Function

Abstract: Naturally occurring CD4+CD25+FOXP3+ regulatory T cells suppress the activity of pathogenic T cells and prevent development of autoimmune responses. There is growing evidence that TLRs are involved in modulating regulatory T cell (Treg) functions both directly and indirectly. Specifically, TLR2 stimulation has been shown to reduce the suppressive function of Tregs by mechanisms that are incompletely understood. The developmental pathways of Tregs and Th17 cells are considered divergent and mutually inhibitory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
141
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 46 publications
15
141
0
Order By: Relevance
“…The endogenous ligand HMGB1 in circulating DNA-containing immune complexes is crucial for anti-dsDNA antibody induction depending on the TLR2/MyD88/miR-155/Ets-1 pathway [13]. TLR2/TLR1 heterodimer stimulation by Pam3Cys can reduce the suppressive activity of Treg cells and drive naive and effector Treg cells into a Th17-like phenotype [14]. Animal studies showed that when compared to C57BL/6lpr/lpr mice, disease manifestations in TLR2-deficient C57BL/6lpr/lpr mice were less severe accompanied by fewer immunological alterations, less renal lesion, and significantly reduced autoantibody titers [5].…”
Section: Increased Expression Of Tlr2 In Cd4 + T Cells From Sle Patiementioning
confidence: 99%
“…The endogenous ligand HMGB1 in circulating DNA-containing immune complexes is crucial for anti-dsDNA antibody induction depending on the TLR2/MyD88/miR-155/Ets-1 pathway [13]. TLR2/TLR1 heterodimer stimulation by Pam3Cys can reduce the suppressive activity of Treg cells and drive naive and effector Treg cells into a Th17-like phenotype [14]. Animal studies showed that when compared to C57BL/6lpr/lpr mice, disease manifestations in TLR2-deficient C57BL/6lpr/lpr mice were less severe accompanied by fewer immunological alterations, less renal lesion, and significantly reduced autoantibody titers [5].…”
Section: Increased Expression Of Tlr2 In Cd4 + T Cells From Sle Patiementioning
confidence: 99%
“…TLR2 forms heterodimers with either TLR1 or TLR6. The identification of TLRs on T cells, and particularly on Tregs, was an important development in the field of innate immune-regulation of adaptive T cell responses (10,13,23,24). We (10) and others (14,25) demonstrated that TLRs modulate the functions of Tregs.…”
mentioning
confidence: 99%
“…The most common approach to defining human Treg subsets is based on combining CD25 and CD127 expression with expression of the classic markers for naive (CD45RA) and memory (CD45RO) conventional T cells (8,9). In addition, based on the expression of CD25 and CD45RA, we (10) and other investigators (8) classified human CD4 + T cells into six subpopulations, fractions (Fr.) I-VI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice immunized with an influenza vaccine adjuvanted with a synthetic TLR-4 agonist via the nasal route, exhibited a transient, enhanced IL-17A pathology, characterized by weight loss and morbidity, which was significantly greater than observed in mice given no-adjuvanted antigen. 41 The effect of adjuvants on induction of tolerance has also been noted; an intranasal co-administration of hen egg lysozyme with a TLR2 ligand enhanced Th1-type antibodies in one case, 118 while another TLG2 ligand, Pam3Cys, was shown to increase the risk of developing autoimmune disease 119 PLGA nanoparticles have been shown to boost tolerance in suppression of arthritis 120 and further research by the same group has shown that they are responsible for generation of enhanced Treg cell induction. 68 …”
Section: Adjuvantsmentioning
confidence: 99%